Nafkah Sebagai Konsekuensi Logis Pernikahan - Darmawan, Darmawan (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2020)
This research aims to find out what are the forms of zahir (material) and inner (non-material) livelihood that a husband must give to his wife? Does the husband provide the living because of the obedience of the wife or because of the marriage contract? By using a qualitative approach. Zahir livelihoods are related to basic daily necessities, which can be classified as clothing, food, shelter, household costs, maintenance, and the cost of children's education. While the inner livelihood can be classified as: 1) Husband teaches the values of tauhid, morality and worship. 2) Husband treats wife well, gently. 3) Husband gives sovereignty to wife to interact with society. 4) The husband gives an explanation of what the wife is lacking. 5) Having an intimate relationship between husband and wife. Livelihood is the logical consequence of the marriage contract, both zahir and inner.Zahir is a gift the husband must give the wife after the marriage contract, provided both fulfill their obligations. Inner livelihood is mandatory support from the husband to the wife until the marriage ends, regardless of her obedience.